2022
DOI: 10.3389/fphar.2022.920514
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin and its nano-formulations: Defining triple-negative breast cancer targets through network pharmacology, molecular docking, and experimental verification

Abstract: Background: Curcumin (CUR) displays the capability of suppressing the proliferation and metastasis of various cancer cells. However, the effects and underline mechanisms of CUR to treat triple-negative breast cancer (TNBC) have not been systematically elucidated with an appropriate method.Methods: In the present research, a combination method of network pharmacology, molecular docking, and in vitro bio-experiment was used to investigate the pharmacological actions and underline mechanisms of CUR against TNBC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Some of the important findings are as follows. NFE2L2 was identified as one of top 10 targets of Curcumin against TNBC [ 22 ]. NLRP3 may mediate the cisplatin induced pyroptosis via activation in TNBC (via activation of MEG3/NLRP3/caspase-1/GSDMD pathway) [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the important findings are as follows. NFE2L2 was identified as one of top 10 targets of Curcumin against TNBC [ 22 ]. NLRP3 may mediate the cisplatin induced pyroptosis via activation in TNBC (via activation of MEG3/NLRP3/caspase-1/GSDMD pathway) [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrate the importance of these TFs and can aim in developing therapeutic strategies for breast cancer treatment. Thirteen genes (AKT1, ARAF, CCND1, EGFR, ERBB2, ERBB3, MTOR, IGF1R, JAK2, MET, PTEN, RAF1, and STAT3) were related to EGFR tyrosine kinase inhibitor resistance (WP4806), which was reported as significant pathway associated with breast cancer [69,84]. Twelve genes (AKT1, CCND1, ERBB2, ESR1, MTOR, IRS1, JAK2, NOS3, PTEN, RAF1, STAT1, and STAT3) were linked to Leptin signaling pathway (WP2034), reported to have a key role in breast cancer tumorigenesis [85].…”
Section: Dataset3mentioning
confidence: 99%
“…Although previous studies have demonstrated curcumin’s capacity to inhibit cell proliferation and invasion in human TNBC MDA-MB-231 cells, [19] the underlying molecular mechanisms are still being explored. This study seeks to bridge this gap in knowledge by employing both bioinformatics and experimental approaches to investigate the effects of curcumin on cell motility in TNBC cell lines, specifically Hs578T and MDA-MB-231 cells.…”
Section: Introductionmentioning
confidence: 99%
“…[13,14] Thus, curcumin may play a significant role in the initiation and progression of various cancers, including breast, lung, and liver cancers, through affecting multiple signaling and molecular pathways, such as Rb, P53, mitogen-activated protein kinase, phosphatidylinositol 3-K (PI3K)/protein kinase B, and NF-kappaB (nuclear factor kappa B cells, NF-κB). [15][16][17][18] Although previous studies have demonstrated curcumin's capacity to inhibit cell proliferation and invasion in human TNBC MDA-MB-231 cells, [19] the underlying molecular mechanisms are still being explored. This study seeks to bridge this gap in knowledge by employing both bioinformatics and experimental approaches to investigate the effects of curcumin on cell motility in TNBC cell lines, specifically Hs578T and MDA-MB-231 cells.…”
Section: Introductionmentioning
confidence: 99%